The Assessment of Adolescent and Youth Health Services in Accordance With Standards for Youth Friendly Health Services of Under Public Health Permanent Secretary Officer - Kasibut, Patcharin; Promprapat, Prakaidao; Ronkaeo, Wannee (Thai Journal of Health Education, 2019)
Promotion of adolescents and youth to access to health information and services according to WHO standards for youth friendly health services (YSHS) will prevent and reduce adolescent pregnancies and health risks among them such as STIs and AIDS, drug addiction and alcoholic beverages, etc. Objectives : To access the implementation of hospitals under the Office of the Permanent Secretary, Ministry of Public Health according to standards for adolescent and youth friendly health services. Procedure : Assessment according to standards for adolescent and youth friendly health services by analyzing both quantitative and qualitative data from reports of visiting and assessing 408 hospitals under Office of the Permanent Secretary, Ministry of Public Health that passed the standards for adolescent and youth friendly health services of 4 components; 1) Management 2) Access to target population and building demands for services 3) Comprehensive services which addresses the needs of the target groups 4) System of services that is efficient and youth friendly. Results : The study found that most hospitals operated all 4 components as mentioned above and also passed the standards with good levels (81.6%, 72.5%, 79.2% and 74.5 respectively). Conclusion : Most hospitals operated according to standards for adolescent and youth friendly health services with a good level 90.4%. The key success factors were administrators’ prioritization by supporting and promoting the implementation of youth friendly health services, the collaboration and support of networks, the expansion of service networks to communities and Tambon health promoting hospitals, the publicity of services that respond to the need of adolescents, the curative and proactive services by counseling and communication through social media. There were obstacles that in some hospitals, health personnel did not give precedence to health promotion due to few staff, heavy workload and personnel turnover. Recommendation : The hospitals’ provision of adolescent and youth friendly health services will be sustainable or not depends on the continuous implementation of hospitals according to the standards and strategies setting to cover more health facilities along with the knowledge exchange among all levels of health facilities.